Water Stress Modulates Soybean Aphid Performance, Feeding Behavior, and Virus Transmission in Soybean - Nachappa, Punya; Culkin, Christopher T.; Saya, Peter M.; Han, Jinlong; Nalam, Vamsi J. (Frontiers in Plant Science, 2016)
Little is known about how water stress including drought and flooding modifies the ability of plants to resist simultaneous attack by insect feeding and transmission of insect-vectored pathogen. We analyzed insect population growth, feeding behaviors, virus transmission, and plant amino acid profiles and defense gene expression to characterize mechanisms underlying the interaction between water stress, soybean aphid and aphid-transmitted, Soybean mosaic virus, on soybean plants. Population growth of non-viruliferous aphids was reduced under drought stress and saturation, likely because the aphids spent less time feeding from the sieve element on these plants compared to well-watered plants. Water stress did not impact population growth of viruliferous aphids. However, virus incidence and transmission rate was lowest under drought stress and highest under saturated conditions since viruliferous aphids took the greatest amount time to puncture cells and transmit the virus under saturated conditions and lowest time under drought stress. Petiole exudates from drought-stressed plants had the highest level of total free amino acids including asparagine and valine that are critical for aphid performance. Aphids did not benefit from improved phloem sap quality as indicated by their lower densities on drought-stressed plants. Saturation, on the other hand, resulted in low amino acid content compared to all of the other treatments. Drought and saturation had significant and opposing effects on expression of marker genes involved in abscisic acid (ABA) signaling. Drought alone significantly increased expression of ABA marker genes, which likely led to suppression of salicylic acid (SA)- and jasmonic acid (JA)-related genes. In contrast, ABA marker genes were down-regulated under saturation, while expression of SA- and JA-related genes was up-regulated. We propose that the apparent antagonism between ABA and SA/JA signaling pathways contributed to an increase in aphid densities under drought and their decrease under saturation. Taken together, our findings suggests that plant responses to water stress is complex involving changes in phloem amino acid composition and signaling pathways, which can impact aphid populations and virus transmission.